2011
DOI: 10.1371/journal.pone.0029601
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis Improved Evidence for Candidate Genes for Intramuscular Fat Percentage from a Genome Wide Association Study of Cattle

Abstract: In genome wide association studies (GWAS), haplotype analyses of SNP data are neglected in favour of single point analysis of associations. In a recent GWAS, we found that none of the known candidate genes for intramuscular fat (IMF) had been identified. In this study, data from the GWAS for these candidate genes were re-analysed as haplotypes. First, we confirmed that the methodology would find evidence for association between haplotypes in candidate genes of the calpain-calpastatin complex and musculus longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 100 publications
1
47
3
5
Order By: Relevance
“…174 On the contrary, a few other GWA have had limited success in the identification of the genetic drivers of IM percentage which could be due to variations including treatments, genetics etc., resulting in the similar phenotype. 175,176 High throughput genomic technologies using powerful SNP panels will have to be combined with phenomics approach to further understand the complexities of IM.…”
Section: Genetic Variations/qtl and Epigenetic Changes Associated Witmentioning
confidence: 99%
“…174 On the contrary, a few other GWA have had limited success in the identification of the genetic drivers of IM percentage which could be due to variations including treatments, genetics etc., resulting in the similar phenotype. 175,176 High throughput genomic technologies using powerful SNP panels will have to be combined with phenomics approach to further understand the complexities of IM.…”
Section: Genetic Variations/qtl and Epigenetic Changes Associated Witmentioning
confidence: 99%
“…The huge number of markers genotyped by the BovineSNP50K Bead Chip [3] provide an ample opportunity for us to perform GWAS in beef cattle. In the past few decades, numerous studies were carried out to map quantitative trait loci (QTLs) responsible for milk production, disease resistance [3, 4], reproduction [5], growth [58], meat quality [912] and carcass traits [1215] in cattle. For carcass traits, previous studies had mapped several QTLs for carcass weights on BTA 6, 8 and 14, where one QTN was detected on BTA 6 and related to the encoding of NCAPG Ile442Met and the others were identified within gene PLAG1-CHCHD7 in the region on BTA14 [16].…”
Section: Introductionmentioning
confidence: 99%
“…One recently developed approach relies on examining how SNPs (single nucleotide polymorphisms) are associated with these qualitative traits [25]. More specifically, this method has been used successfully in studies that examined fat-related traits, such as intramuscular fat percentage, marbling, rib fat, backfat thickness and rump fat depth [26-35]. By the use of high-density SNP panel assays for different breeds and crosses, these studies have collectively found such traits associated with regions on nine bovine chromosomes (6, 15, 17, 20, 21, 24, 25, 26, and 28) [27,28,32,35].…”
Section: Introductionmentioning
confidence: 99%